Konsep Penciptaan Manusia Dalam Perspektif Ronggowarsito - M. Kharis Majid; Tamara Ajwa Salsabila (Sutasoma : Jurnal Sastra Jawa, 2023)
Each faith has its own belief in the process of human creation, and this research will discuss the concept of the creation of the first human in Ronggowarsito's view by reviewing a few stories written in the Paramayoga fiber. This research aims to show the practice of the concept of human creation with the concept of Wihdatu-l-wujud or Manunggaling Kawulo Gusti and to review the concept of the creation of the first human from the perspective of the Javanese poet Rg. Ronggowarsito. The method used in this library research is qualitative analytical descriptive using a text approach model as well as a philosophical and historical approach. From this research it can be concluded that Ronggowarsito concluded that humans were created with seven dignities which at the end point are a manifestation of God and his servants and this is what is called the Manunggaling Kawulo Gusti concept. In the Paramayoga fiber, it is told about Adam as the first human with many very strong syncretic manifestations between Javanese, Hindu and Islamic traditions. From this mixing, a practice emerged from the concept of human creation in Ronggowarsito's view. Keywords: Ronggowarsito, Human Creation, Java.